The role of technology in developing thematic learning evaluation tools at Junior High School - Wasul Nuri (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
Rapid technological developments have had a significant impact on various aspects of education, including the development of thematic learning evaluation tools in junior high schools (SMP). This article explores how technology can be used to increase effectiveness and efficiency in thematic learning evaluation at the junior high school level. On the one hand, technology offers great opportunities such as automation of assessments, deeper data analysis, and increased interactivity and student engagement. However, on the other hand, the challenges faced include the availability of infrastructure, the readiness of teachers and students to adapt to technology, as well as issues of data privacy and security. This article provides a comprehensive overview of existing challenges and opportunities, as well as offers recommendations for optimal use of technology in evaluating thematic learning at the junior high school level. The development of the current technological era has helped many fields, especially education. One of those affected is the evaluation part of learning. Learning evaluation tools have emerged as a result of the integration of technology. This paper aims to reveal the potential and obstacles to developing thematic learning evaluation tools in the future. The method used in this research process is qualitative, library type. Data collection uses documentation techniques and data analysis using the Miles & Huberman method, namely: data reduction, data display, and conclusion. Data shows that there are several potentials and challenges using AI, VR, & AR technology in learning evaluation.